2019
DOI: 10.14203/jep.27.2.2019.11-25
|View full text |Cite
|
Sign up to set email alerts
|

Studi Environmental Kuznets Curve Di Asia: Sebelum Dan Setelah Millennium Development Goals

Abstract: Pencemaran lingkungan dapat menurunkan kesejahteraan subyektif (subjective well-being). Studi ini bertujuan membuktikan berlakunya hipotesis Environmental Kuznets Curve (EKC) di negara-negara berpendapatan tinggi dan menengah Asia, juga untuk menganalisis perbedaan pengaruh GDP per kapita, konsumsi energi, dan populasi penduduk pada emisi CO2 di wilayah yang sama pada periode sebelum dan setelah MDGs. Data diperoleh dari World Bank dengan periode waktu 1987-2014, di mana analisisnya menggunakan metode kuantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 0 publications
3
11
1
3
Order By: Relevance
“…The higher the level of economic growth of a country, the higher the level of awareness in each country of its concern for the environment, especially CO2 emissions. This study is in line with that conducted by Arouri, Hossain, and Badrul Muttakin (2014), Ali, Soemarno, and Purnomo (2015), Ibrahiem (2016), andNikensari, Destilawati, andNurjanah (2019).…”
Section: A'yun and Khasanahsupporting
confidence: 92%
“…The higher the level of economic growth of a country, the higher the level of awareness in each country of its concern for the environment, especially CO2 emissions. This study is in line with that conducted by Arouri, Hossain, and Badrul Muttakin (2014), Ali, Soemarno, and Purnomo (2015), Ibrahiem (2016), andNikensari, Destilawati, andNurjanah (2019).…”
Section: A'yun and Khasanahsupporting
confidence: 92%
“…EKC theory focuses on environmental degradation such as air pollution and deforestation (Mosconi et al, 2020). The stages of the EKC theory are divided into 3 stages, namely the pre-industrial economy, the industrial economy, and the post-industrial economy where the economy is dominated by the service sector (Nikensari et al, 2019).…”
Section: Kuznets Curve Ens Environmental Theorymentioning
confidence: 99%
“…Previous research has several times discussed the determinants of deforestation in a country, mainly related to economic growth, but there are still differences in results. The Environmental Kuznets Curve (EKC) states that initially economic growth has the effect of increasing environmental degradation until it reaches a point where people realize the need for better environmental quality so that environmental degradation will decrease (Nikensari et al, 2019). Previous research has shown that there is a directly proportional relationship between economic growth and deforestation (Ahmed et al, 2015;Faria & Almeida, 2016;Nathaniel & Bekun, 2020;Yameogo, 2021).…”
Section: Introduction *mentioning
confidence: 99%
“…Economic growth cannot solve environmental problems (Aydin & Esen, 2017). Fasikha & Yuliadi (2018) There are indications that high-income countries will be able to reduce CO2 emissions after reaching the turning point, while lower-middle-income countries will still be unable to reduce CO2 emissions even though they have exceeded the turning point (Apergis et al, 2017;Nikensari et al, 2019). Middle development countries have an inverted U curve characteristic, while developed countries and low development countries are indicated to have no turning point, or CO2 emissions, and environmental damage will continue to increase (Yustisia & Sugiyanto, 2014).…”
Section: Environment and Kuznets Curvesmentioning
confidence: 99%
“…the inverted U hypothesis on environmental issuesA quadratic nonlinear regression model is used to determine the projected decline(Cahyadin et al, 2021;Nikensari et al.Based on equations 2 and 5, to estimate the validity of the inverted Kuznets U curve hypothesis, it is based on the following conditions: If < 0, there is an inverted U-shaped relationship If > 0, there is no inverse U-shaped relationship This study uses a 95% Confident Interval or 0.05 RESULT AND DISCUSSION A. Economic Growth in Jambi Province Jambi province's economic growth during the 2010-2021 period had a positive trend, except in 2020, this year's economic growth contracted by -0.44% due to the COVID-19 pandemic.…”
mentioning
confidence: 99%